Epsilon Medical Devices Sdn Bhd / Nur Zuhirah Sabaruddin - Sabaruddin, Nur Zuhirah (Faculty Of Chemical Engineering, 2021)
For the past 17 weeks having industrial training in Epsilon Medical Devices SON BHD, I have undoubtedly gained so many experiences, knowledge and skills. Being appointed in Quality Assurance Department conveyed to me a grasp and understanding of the importance of quality control and assurance of products. Every product from the raw material until finishing need to be careful and thorough tested and inspected before run in the production and release to the markets. I was exposed to the process of the developing new products, managed documentation of validation protocols, handled machines such as Universal Testing Machine and Friction Tester Machine, and understood some part of mechanism in industrial medical devices from management, production, technical, quality and shipping department. I have taken chances to observe the real situation and environment that happened in the manufacturing company. Other than that, I developed tremendous skills including products knowledge of medical devices, testing, computer skills in Microsoft Office and software machines, adaptability, attention to detail on doing the testing and inspection, data entry, filing and paper management, and machine learning. I have earned trustworthiness to handle the products testing on my own and prepared documentation. I was active listening on orders given out by the supervisor, accessing and analyzing information also established commitment. Regarding my interaction skills, all the staffs in EMO were sociable and kind despite their ages and races. This helped to boost my communication skills as the intern student. To conclude, the purpose of industrial training was achieved as it showed the student was capable to dive in industrial working surrounding and profits with all the knowledge and skills. Consequently, the scope discovered Quality Assurance department was much related to the course undertaken by the student which was CHE227 Product Design and Development in semester 5 of Diploma in Chemical Engineering. It benefits to practise and sharpen the theories received in classes into the training.